"From the Moment I Made My Wedding Vows My Suffering Began": Calidad in the Nineteenth‐Century Mexican Borderlands. Issue 3 (5th September 2018) - Starling, Jamie
Abstract: Bárbara Aguirre's divorce case in Chihuahua, Mexico during the 1830s provides a case study of how people of this northern frontier state debated ideas about gender, class, race, and honor in the complex social matrix of calidad. Calidad provided a framework in which Aguirre and her estranged spouse, Francisco Velarde, contested each other's claims before authorities and the larger community of Paso del Norte. In a series of testimonies that comprise some of the most extensive statements by a woman of the Mexican borderlands in this era, Aguirre boldly asserted her rights as a citizen and property owner in the face of an abusive husband. Nevertheless, Aguirre had to negotiate a highly patriarchal order where male legal counsel, witnesses, priests, and civil officials stood in judgment of her personal conduct and methodically verified her claims of physical and emotional abuse. This article illustrates how residents of northern Mexico engaged calidad and attendant concepts of gender and social status in their everyday lives during a time of rapid political and social change. As such, it contributes to a better understanding of the social history of Mexico's northern borderlands and Latin America at large during the age of independence and national formation.